2011
DOI: 10.1029/2010jf001921
|View full text |Cite
|
Sign up to set email alerts
|

The landslide stage of the Hsiaolin catastrophe: Simulation and validation

Abstract: [1] Typhoon Morakot struck southern Taiwan in the summer of 2009, causing the most severe flooding since the 1950s. In the early morning of August 9, rainfall triggered the Hsiaolin landslide, and the resulting debris avalanche covered the township of Hsiaolin Village, Kaohsiung. Around five hundred people were buried alive. Reconstruction of the runout of the debris avalanche would increase understanding of the large-scale avalanches for future hazard mitigation purposes. Simulation of the debris avalanche ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 64 publications
(119 reference statements)
2
44
0
Order By: Relevance
“…Furthermore, such a destruction frontier indicates a major flow direction along the NE to the SW for the sliding of materials into Siaolin Village. Such an inference based on the magnetic survey is supported by a very recent simulation of the Siaolin landslide by Kuo et al (2010). The magnetic observations in this study thus provide a relevant constraint for further numerical simulation (e.g., Crosta et al, 2004;Kuo et al, 2009) of the flow pattern of the Siaolin landslide event (Kuo et al, 2010).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 51%
“…Furthermore, such a destruction frontier indicates a major flow direction along the NE to the SW for the sliding of materials into Siaolin Village. Such an inference based on the magnetic survey is supported by a very recent simulation of the Siaolin landslide by Kuo et al (2010). The magnetic observations in this study thus provide a relevant constraint for further numerical simulation (e.g., Crosta et al, 2004;Kuo et al, 2009) of the flow pattern of the Siaolin landslide event (Kuo et al, 2010).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 51%
“…Hui et al, 1999). For further details of the numerical implementation, the readers are referred to Tai and Lin (2008); Tai et al (2011).…”
Section: Numerical Investigationmentioning
confidence: 99%
“…Taking advantage of the introduction of the UC system and the concept of general topography in Bouchut and Westdickenberg (2004), Tai and Kuo (2008) proposed a singlephase model with a deformable coordinate system for twodimensional mountain slopes, where the coordinate ζ = 0 always coincides with the varying topographic surface. A single-phase model for a three-dimensional topography was proposed by Tai et al (2012), and it is capable of successfully resolving the real catastrophic Hsiaolin landslide (Taiwan), see Kuo et al (2011). The present study is a Coulombmixture extension of Tai et al (2012)'s work with temporally varying coordinates for the entrainment-deposition processes.…”
Section: Y C Tai and C Y Kuo: Debris Flows Of The Coulomb-mixturementioning
confidence: 99%
See 1 more Smart Citation
“…The major slid mass on the east side of the Cishan River is www.intechopen.com best-fit algorithm to minimize the difference between the simulation and the field measurement, it is confirmed that the optimal value of the friction coefficient is 11.5 o , with just a minute offset from the straightforward estimation. Fuller theoretical and numerical details of the simulation have been reported in a designated paper (Kuo et al, 2011). Two snapshots at t = 32 and t = 60 seconds are shown in Figures 3A and 3B, respectively.…”
Section: Simulation Of Siaolin Landslidementioning
confidence: 99%